A case of labio-facial necrotizing fasciitis complicating acne. (December 2016) - Eltayeb, Amel; Ahmad, Abdelnasir; Elbeshir, Elnour
Abstract Background Facial necrotizing fasciitis is extremely rare. Most of the cases reported in literature are related to dental, sinus, tonsillar and salivary glands causes, but rarely as consequence of skin infection. We report a unique case of lower lip cellulitis, which was initially misdiagnosed as angioedema and subsequently progressed into lower lip necrotizing fasciitis. Case presentation This is a case report of necrotizing fasciitis involving the lower lip as a consequence of infected skin acne in a 19 year old black female. The patient had been diagnosed earlier as a case of angioedema by a physician and treated accordingly. She was mildly anemic, hyponatremic and hypokalemic. Treatment was started immediately by incision, drainage and full debridement of the whole necrotic tissue. Triple antibiotic therapy was administered and daily irrigation and dressing were performed until full recovery. Complete healing occurred within a month by secondary intention. Conclusion This case demonstrates the misdiagnosis of a lip swelling leading to the development of labiofacial necrotizing fasciitis, a serious and life threatening condition. Lip angioedema is a common condition; however, lip fasciitis is rare. A broad differential diagnosis in case of lower lip swelling is essential to avoid inappropriate treatment delay.